The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1177/0891243219865510
|View full text |Cite
|
Sign up to set email alerts
|

How Cities Erode Gender Inequality: A New Theory and Evidence from Cambodia

Abstract: Support for gender equality has increased globally, and studies of this trend usually examine individual- and/or country-level factors. However, this overlooks subnational variation. City-dwellers are more likely to support gender equality in education, employment, leadership, and leisure. This article investigates the causes of rural–urban differences through comparative, qualitative research in Cambodia. The emergence of rural garment factories presents a quasi-natural experiment to test the theory that fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 61 publications
(68 reference statements)
0
22
1
Order By: Relevance
“…The literature has also suggested that metropolitan areas are at the vanguard of social change (e.g. Glaeser, 2012;Evans, 2019). However, we found no significant differences when comparing respondents' areas of residence.…”
Section: Effects Of the Social Crisiscontrasting
confidence: 69%
“…The literature has also suggested that metropolitan areas are at the vanguard of social change (e.g. Glaeser, 2012;Evans, 2019). However, we found no significant differences when comparing respondents' areas of residence.…”
Section: Effects Of the Social Crisiscontrasting
confidence: 69%
“…A possible explanation is that rural mothers may have had less influence and exposure to breastmilk substituents via media marketing than urban mothers who may have mistakenly derived the value of breastmilk substitutes from its modernity [18,19]. In addition, because of greater job opportunities in urban regions and that Cambodians who value working tend to move from rural to urban areas to live, urban mothers tend to prioritize nondomestic work more than rural mothers [25,26]. Urban mothers are therefore likely to spend less time domestically than their rural counterparts, leaving them less opportunity to exclusively breastfeed their infants.…”
Section: Discussionmentioning
confidence: 99%
“…The independent variables included in the analysis were classified into sociodemographic characteristics and maternal healthcare access and behavioral factors. The sociodemographic variables were residence (urban, rural), maternal age (<18, [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49], maternal education (no schooling, primary school, secondary school/higher), current marital status (currently married/in union, formerly married), employment status (no job/not working, agricultural/self-employed, professional/technical/sales, others), wealth index (low, middle, high), religion (Buddhist, others), infant birth weight (<2500 grams, ≥2500 grams), infant birth order, sex of infant, infant age, and singleton child status. Wealth index was categorized into low, middle, and high, based on the CDHS 2014 classification of wealth quintiles.…”
Section: Independent Variablesmentioning
confidence: 99%
“…However, case study research has shown evidence for the presence of more localized gender norms. Many studies have identified differences in norms between rural and urban areas (Evans 2019), while others have documented how local gender norms shape individuals' attitudes and patterns of behavior (Brown-Saracino 2017;Correll et al 2017;Guenther 2010). Taken together, research on the consequences of gender norms has focused on local dynamics, while studies on spatial variation have primarily examined countrylevel attributes.…”
Section: Gendered Places: the Dimensions Of Local Gender Norms Acrossmentioning
confidence: 99%
“…Yet, a growing number of studies have identified the presence of more localized gender norms. Research in Africa (Charles 2020; Evans 2018) and Southeast Asia (Evans 2019) has identified differences between rural areas with more traditional gender norms and urban centers where women’s educational advancement and employment are widely supported. Many studies have compared the gender norms between East and West Germany (Dirksmeier 2015; Guenther 2010).…”
Section: From Global To Local: Spatial Variation In Gender Normsmentioning
confidence: 99%